2021
DOI: 10.1590/1981-6723.32219
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of inactivation of foodborne bacterial pathogens in serrano artisanal cheese during ripening

Abstract: Serrano artisanal cheese is a traditional raw milk dairy product from southern Brazil. For safe consumption of raw milk products, ripening is a critical period for reducing populations of pathogenic and spoilage microorganism and, then, the knowledge on inactivation kinetics of microorganisms is necessary to guarantee food safety and quality. In the present work, inactivation kinetics of foodborne bacterial pathogens required by Brazilian regulations in serrano artisanal cheeses were statistically evaluated du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 25 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Population reduction of foodborne bacteria during ripening of serrano cheese was evaluated and results showed that dairy products are free of Salmonella spp., E. coli and L. monocytogenes through the maturation period. Pretto and coauthors [10] also observed the absence of Salmonella spp. and L. monocytogenes on SAC, although is not rare to find these bacteria on artisanal dairy products [19][20].…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Population reduction of foodborne bacteria during ripening of serrano cheese was evaluated and results showed that dairy products are free of Salmonella spp., E. coli and L. monocytogenes through the maturation period. Pretto and coauthors [10] also observed the absence of Salmonella spp. and L. monocytogenes on SAC, although is not rare to find these bacteria on artisanal dairy products [19][20].…”
Section: Resultsmentioning
confidence: 89%
“…Souza and coauthors [9] observed that serrano artisanal cheeses' ripening process should be longer than 30 days, but not necessarily 60 days, in order to allow microbiological stabilization. Pretto and coauthors [10] observed that ripening SAC for 33 days is enough to reach a safe foodborne microbial pattern. But there is still the need for food science and technology efforts to properly produce SAC products safely with a low ripening time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in most studies, Salmonella sp. [ 12 , 15 , 18 , 28 , 33 , 35 , 36 , 48 , 49 ] and L. monocytogenes [ 10 , 13 , 18 , 33 , 36 , 40 , 48 , 49 ] were absent in the various kinds of artisanal cheese surveyed. It is worth noting, though, that Allaion et al [ 34 ] detected 8 positive samples (out of 100) for Salmonella by PCR, but only one was confirmed by the culture-dependent method.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the Serrano cheese produced in Santa Catarina state, two of the studies in the reviewed literature [ 15 , 41 ] demonstrated that 60 days of ripening may not be enough to meet the legal parameters since L. monocytogenes was present at 35 [ 41 ] and 60 days [ 15 ] of ripening. However, for Serrano cheese produced in Rio Grande do Sul state, Souza et al [ 68 ], Pretto et al [ 48 ], and Ströher et al [ 49 ] indicated a minimum ripening time ranging from 30 to 33 days, which is a much shorter ripening period that can still reach acceptable microbiological levels than those required by Normative Instruction SEAGRI N° 7 [ 63 ]. It is important to highlight that Ströher et al [ 49 ] demonstrated that the refrigerated temperature (5 °C) determined by IN 7/2014 is not adequate for ripening this type of cheese.…”
Section: Introductionmentioning
confidence: 99%